The Discipline Enforcement at the Education and Culture Office of Lahat Regency - Meri Asyanti; Yusri Yusri; Amaludin Amaludin (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The Education and Culture Office of the Lahat Regency as an institution that provides services in the education sector seeks to improve personnel services to create professional, reliable, honest, clean, and responsible Civil Servants. The main problem in this study is "How is Discipline Enforcement at the Education and Culture Office of Lahat Regency?". This study uses a qualitative approach. Civil Servants do not implement this Government Regulation because of the character of the civil servants themselves, due to the lack of mindset of the civil servants themselves, to comply with these regulations. So that it has an impact on the performance of the State Civil Apparatus in improving the performance of employees in the Education and Culture Office of the Lahat District. The firmness of the leadership is not maximized so there are still several employees at the Department of Education and Culture who are still not efficient in completing the assigned tasks and responsibilities. Supervision is not optimal, so there are still employees who underestimate the instructions from the leadership. In terms of imposing sanctions on Civil Servants, it has been carried out according to Government Regulation Number 53 of 2010 concerning the Discipline of Civil Servants. But it still needs to be improved.